Children’s understanding of COVID-19 spread and its preventive strategies in Uganda: a cross sectional study among children aged 10 to 13 years in Hoima District - Christine Nalwadda Kayemba; Lydia Kabwijamu; Maxencia Nabiryo; Andew Tusubira; Justine Bukenya; Sarah Bunot; Juliet Kiguli (Journal of Interventional Epidemiology and Public Health)
Introduction: The control of COVID-19 among children is mainly dependent on preventive strategies including proper use of facemask s, hand hygiene etiquette and social distancing. Despite ongoing risk communication, it is not clear how children understand COVID-19 and the control measures. We described children's understanding of COVID-19 transmission and the preventative strategies in Uganda.